Health‐related quality of life of COVID‐19 patients after discharge: A multicenter follow‐up study. Issue 11 (17th March 2021) - Qu, Guangbo; Zhen, Qi; Wang, Wenjun; Fan, Song; Wu, Qibing; Zhang, Chengyuan; Li, Bao; Liu, Gang; Yu, Yafen; Li, Yonghuai; Yong, Liang; Lu, Baojing; et al.
Abstract: Aims and Objectives: To determine the health‐related quality of life (HRQoL) of COVID‐19 patients after discharge and its predicting factors. Background: COVID‐19 has caused a worldwide pandemic and led a huge impact on the health of human and daily life. It has been demonstrated that physical and psychological conditions of hospitalised COVID‐19 patients are impaired, but the studies focus on physical and psychological conditions of COVID‐19 patients after discharge from hospital are rare. Design: A multicentre follow‐up study. Methods: This was a multicentre follow‐up study of COVID‐19 patients who had discharged from six designated hospitals. Physical symptoms and HRQoL were surveyed at first follow‐up (the third month after discharge). The latest multiple laboratory findings were collected through medical examination records. This study was performed and reported in accordance with STROBE checklist. Results: Three hundred eleven patients (57.6%) were reported with one or more physical symptoms. The scores of HRQoL of COVID‐19 patients at third month after discharge, except for the dimension of general health, were significantly lower than Chinese population norm ( p  < .001). Results of logistic regression showed that female (odds ratio (OR): 1.79, 95% confidence interval (CI): 1.04–3.06), older age (≥60 years) (OR: 2.44, 95% CI: 1.33–4.47) and the physical symptom after discharge (OR: 40.15, 95% CI: 9.68–166.49) were risk factors for poor physical component summary; the physical symptom after discharge (OR: 6.68, 95% CI: 4.21–10.59) was a risk factor for poor mental component summary. Conclusions: Health‐related quality of life of discharged COVID‐19 patients did not come back to normal at third month after discharge and affected by age, sex and the physical symptom after discharge. Relevance to clinical practice: Healthcare workers should pay more attention to the physical and psychological rehabilitation of discharged COVID‐19 patients. Long‐term follow‐up on COVID‐19 patients after discharge is needed to determine the long‐term impact of COVID‐19.